New arsenate minerals from the Arsenatnaya fumarole, Tolbachik volcano, Kamchatka, Russia. IV. Shchurovskyite, K2CaCu6O2(AsO4)4 and dmisokolovite, K3Cu5AlO2(AsO4)4. (2nd January 2018) - Pekov, Igor V.; Zubkova, Natalia V.; Belakovskiy, Dmitry I.; Yapaskurt, Vasiliy O.; Vigasina, Marina F.; Sidorov, Evgeny G.; Pushcharovsky, Dmitry Yu
Abstract: Two new minerals shchurovskyite, ideally K2 CaCu6 O2 (AsO4 )4, and dmisokolovite, ideally K3 Cu5 AlO2 (AsO4 )4, are found in sublimates of the Arsenatnaya fumarole at the Second scoriacone of the Northern Breakthrough of the Great Tolbachik Fissure Eruption, Tolbachik volcano, Kamchatka Peninsula, Russia. They are associated with one another and with johillerite, bradaczekite, tilasite, melanarsite, tenorite, hematite, aphthitalite, langbeinite, orthoclase, etc. Shchurovskyiteoccurs as coarse tabular or prismatic crystals up to 0.15 mm in size or anhedral grains forming parallel aggregates and crusts up to 1.5 cm × 2 cm across. Dmisokolovite forms tabular, prismatic or dipyramidal crystals up to 0.2 mm in size, commonly combined in clusters or crusts up to0.7 cm × 1.5 cm across. Both minerals are transparent with a vitreous lustre. They are brittle, with Mohs' hardness ≈3. Shchurovskyite is olive-green or olive drab. Dmisokolovite is bright emerald-green to light green. D calc = 4.28 (shchurovskyite) and 4.26 (dmisokolovite)g cm –3 . Both are optically biaxial; shchurovskyite: (+), α = 1.795(5), β = 1.800(5), γ = 1.810(6), 2Vmeas = 70(15)°; dmisokolovite: (–), α = 1.758(7), β = 1.782(7), γ = 1.805(8), 2Vmeas = 85(5)°. The Ramanspectra are given. Chemical data (wt.%, electron-microprobe; first value is for shchurovskyite, second for dmisokolovite): Na2 O 0.00, 0.83; K2 O 8.85, 10.71; Rb2 O 0.11, 0.00; MgO 0.00, 0.35; CaO 4.94, 0.21; CuO 43.19, 38.67; ZnO 0.42, 0.20; Al2 O3 0.04, 4.68; Fe2 O3 0.00, 0.36; P2 O5 0.59, 0.78; V2 O5 0.01, 0.04; As2 O5 40.72, 43.01; SO3 0.35, 0.00; total 99.22, 99.84. The empirical formulae, based on 18 O a.p.f.u., are shchurovskyite: K2.05 Rb0.01 Ca0.96 Cu5.92 Zn0.06 Al0.01 P0.09 S0.05 As3.86 O18 ;dmisokolovite: Na0.28 K2.36 Mg0.09 Ca0.04 Cu5.04 Zn0.04 Al0.95 Fe0.05 3+ P0.11 As3.88 O18 . The strongest reflections of X-ray powder patterns [ d, Å( I )( hkl )]are shchurovskyite: 8.61(100)(200, 001), 5.400(32)(110), 2.974(32)(312, 510), 2.842(47)(003, 020), 2.757(63) (601, 511), 2.373(36)(512, 420) and 2.297(31)(421, 222, 313); dmisokolovite: 8.34(95)(002), 5.433(84)(110), 2.921(66)(510, 314), 2.853(58)(511, 020) and 2.733(100)(006, 512, 602). Shchurovskyiteis monoclinic, C 2, a = 17.2856(9), b = 5.6705(4), c = 8.5734(6) Å, β = 92.953(6)°, V = 839.24(9) Å 3 and Z = 2. Dmisokolovite is monoclinic, C 2/ c, a = 17.0848(12), b = 5.7188(4), c =16.5332(12) Å, β = 91.716(6)°, V = 1614.7(2) Å 3 and Z = 4. Their crystal structures [single-crystal X-ray diffraction data, R = 0.0746 (shchurovskyite) and 0.1345 (dmisokolovite: model)] are closely related in the topology of the main buildingunits. They are based on a quasi-framework consisting of AsO4 tetrahedra and polyhedra centred by Cu in shchurovskyite or by Cu and Al in dmisokolovite. K and Ca are located in channels of the quasi-framework. The minerals are named in honour of outstanding Russian geologists andmineralogists Grigory Efimovich Shchurovsky (1803–1884) and Dmitry Ivanovich Sokolov (1788–1852).